RULES OF ORGANIZATION SOCIAL-ROLE INTERACTION OF STUDENTS TO IMPROVE THEIR INTERCULTURAL COMMUNICATIVE COMPETENCE - Valeriya S. Suyskaya; Mariya V. Kharlamova (Высшее образование в России)
Social-role interaction is a form of organization of communication in the classroom by exchanging of information in an artificial language environment. Pragmatic factors of the communicative situation, the role andactions in the foreign language community standards of conduct are set outside. Students communicate in the proposed situations in accordance with accepted standards. At the same time in the communication process, students identify themselves with a given role, interpreting the methods and standards of behavior that are typical for the role of foreign language culture, from the perspective of their own ideas, experiences and values. «Living» this role, students realize the effects of foreign culture, and thus perceive it, which generally contributes to the formation of their intercultural communicative competence. The article gives an analysis of the problems reported by teachers in the organization of social-role interaction during foreign language lessons. Describes the ways and techniques in order to improve social-role interaction aimed at improving cross-cultural communicative competence of students. Socio-role interaction does not take much time, if teacher has a clear purpose, theknowledge ofthe basicrules and compliance milestones. These stages are: 1) motivation, 2) the creation of social and cultural background of the interaction of languages and cultures, 3) cooperation in cross-cultural interaction, 4) the presentation of group decisions, and 5) reflection.